Fatwa Communication in the Digital Era: Synergy of Conventional Media and Digital Technology in Disseminating the Fatwa on ‘Uang Panai’ by the MUI of South Sulawesi - Azka, Ibnu; Baldan Haramain, Fathur (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2025)
This study aims to analyze the communication strategy used by the Indonesian Ulema Council (MUI) of South Sulawesi in disseminating fatwas related to dowry in the digital era. Panai, as a tradition of the Bugis-Makassar community in marriage, often causes polemics related to the amount of value that is considered burdensome. The MUI of South Sulawesi plays a role in providing religious guidance through fatwas, which must be disseminated effectively to the wider community. This study uses a qualitative approach with a case study method, where data is collected through interviews, document analysis, and observation. This study focuses on how digital technology, such as social media and online platforms, is utilized to reach a wider audience, as well as the challenges faced in conveying religious messages in the modern era. The results of this study indicate that the MUI South Sulawesi communication strategy elaborates conventional and digital approaches, which include optimizing social media, collaborating with community leaders, and disseminating information through the official website. This study suggests further development in terms of digital innovation and increasing digital literacy to ensure that fatwas can be understood and well received by all groups.